(untitled) - Nielsen, Joyce McCarl (Prospect Heights, Ill., 1990)
Includes bibliographical references (p. 261-275) and index.; Rev. ed. of: Sex in society. c1978; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Sex role; Social status; Vai trò giới tính; Địa vị xã hội